Pembangunan Infrastuktur Jaringan Internet Pada Sekolah SMKN 3 Depok Untuk Mendukung Pembelajaran Daring – Luring Guna Meningkatkan Mutu Para Siswa dan Guru Di SMKN 3 Depok - Daffa Anas Darman; Sherina Nurul Kautsar; Muhammad Izzaturrahman; Mia Kamayani (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2023)
Progress in the field of innovation and data is very broad and high, especially in an advanced world like this, of course internet networks are very important and needed by all levels of society, of course this is very beneficial for educational organizations, especially SMKN Sekolah 3 Depok which is located on Jalan Abadi. Jaya, Sukmajaya area, Depok city. Along with the increasing need for learning and practice performances, improvements have been made to the web network foundation in schools and in train ing areas to add web networks and preparation of instructions so that educators can overcome problems that occur in schools. PC organization. Implementing an adequate web network framework to assist online and offline education and learning practices while accelerating the continuation period 4.0, as well as assisting educators in developing their capacity in the fields of innovation and data.